2015
DOI: 10.1534/genetics.115.181008
|View full text |Cite|
|
Sign up to set email alerts
|

The Double-Reduction Landscape in Tetraploid Potato as Revealed by a High-Density Linkage Map

Abstract: The creation of genetic linkage maps in polyploid species has been a long-standing problem for which various approaches have been proposed. In the case of autopolyploids, a commonly used simplification is that random bivalents form during meiosis. This leads to relatively straightforward estimation of recombination frequencies using maximum likelihood, from which a genetic map can be derived. However, autopolyploids such as tetraploid potato (Solanum tuberosum L.) may exhibit additional features, such as doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 43 publications
8
104
0
Order By: Relevance
“…Double reduction refers to the fact that for a specific locus, the sister alleles come together in the same gamete during meiosis. It has been reported that the rate of double reduction is expected to increase towards the telomeres (Koning-Boucoiran et al, 2012; Bourke et al, 2015). In our study, the loci that showed this peculiar pattern of segregation are located at the extremity of LG3 (IPAHM103 and IPAHM282) and LG7 (RN13D04).…”
Section: Discussionmentioning
confidence: 99%
“…Double reduction refers to the fact that for a specific locus, the sister alleles come together in the same gamete during meiosis. It has been reported that the rate of double reduction is expected to increase towards the telomeres (Koning-Boucoiran et al, 2012; Bourke et al, 2015). In our study, the loci that showed this peculiar pattern of segregation are located at the extremity of LG3 (IPAHM103 and IPAHM282) and LG7 (RN13D04).…”
Section: Discussionmentioning
confidence: 99%
“…Tetraploid populations derived from crosses between ornamental varieties display complex patterns of inheritance that complicate not only genetic analysis but also map construction and require many more markers (Bourke et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The probabilities obtained from TetraOrigin are much larger than those from H2013. TetraOrigin (fullModel) indicates that the average double-reduction probability is around 0.04, larger than the estimate based only on a subset of markers of a different potato mapping population (Bourke et al 2015). As expected, double reduction occurs more frequently at the telomeres than near the centromere ( Figure 6D).…”
Section: Comparisons Using Real Potato Datamentioning
confidence: 59%